Grindr Wars: Race, Caste, and Class Inequalities on Dating Apps in India and South Africa - Philip, Shannon (Ethnoscripts, 2024)
The rapid digitalisation, neoliberalisation, and globalisation in countries like India and South Africa are profoundly transforming the sexual identities and sexual politics of these Global South contexts. In particular, dating apps like Grindr are changing the ways in which young gay men’s identities and relationships are formed, mediated, and embodied. In this article, I ethnographically explore the ways in which Grindr offers much needed visibility to young middle-class gay men in India and South Africa where powerful heteropatriarchies marginalise their sexualities and masculinities. Yet at the same time, the inequality that marks this digital and neoliberal expansion means that gay dating applications like Grindr also reproduce these very inequalities of race, caste, and class. I reveal in particular the growing commodification of gay identities and sexualities that is mediated through digital platforms, producing a hierarchy between ‘classy gays’ and ‘poor gays’. Desire itself becomes commodified wherein ‘poor gays’ are not desirable bodies or identities and the performance of class and consumption becomes central to claims of sexual desirability. Grindr’s geolocating technology allows middle-class gay men to discriminate against ‘poor gays’ through the spatial and urban inequalities of cities like Delhi and Johannesburg, further amplifying the inequalities of race, caste, and class. In this context, ‘Grindr Wars’ take place, which reveal the social and symbolic tensions, clashes, and violences that shape queer life in India and South Africa today.